Health Care in Java : Past and Present - Boomgaard, Peter, (sian Studies - Book Archive pre-2000., 1996)
The study of health and illness in Indonesia has long been an expanding field for scholars with a medical or social science background, both in Indonesia and abroad. European interest in this topic has increased considerably during recent decades. The articles presented in this volume highlight the cultural, political, economic, and social framework within which theory and practice of health care in Java operate at present and in the past.